MEME-based Assemblr Edu Microlearning Enhance Student’s Cognitive Ability - Anna Mariyani; Aqidatul Munfariqoh; Novita Imania Rahma; Crisanto Alao Daing (Universitas Muhammadiyah Makassar, 2026)
The growing demand for flexible, interactive, and cognitively engaging digital learning requires instructional models that align with the learning characteristics of Generation Z and Alpha students. This study aimed to examine the effect of microlearning supported by the Assemblr Edu application and structured through a Multi-Entry Multi-Exit (MEME) approach on students’ cognitive abilities in Mathematics Education. A quantitative quasi-experimental design was employed using a non-equivalent pretest–posttest control group design. The participants were 68 third-semester students from the Elementary School Teacher Education Program at STKIP Muhammadiyah Blora, consisting of 35 students in the experimental class and 33 students in the control class. The experimental class received microlearning activities using the MEME-based Assemblr Edu application, whereas the control class received conventional instruction. Data were collected through cognitive ability tests and analyzed using the Liliefors normality test, F-test for homogeneity, independent-samples t-test, and normalized gain analysis. The findings showed that the experimental class achieved a higher posttest mean score (78.22; SD = 9.03) than the control class (68.41; SD = 11.82). The t-test result indicated a significant difference between groups, with t-value = 3.43 exceeding t-table = 2.00. The normalized gain score of the experimental class was 0.51, compared with 0.31 in the control class, indicating stronger cognitive improvement. These results demonstrate that MEME-based Assemblr Edu microlearning positively affects students’ cognitive abilities. The novelty of this study lies in integrating microlearning, augmented reality-based digital media, and the MEME learning pathway in Mathematics Education. This study contributes an empirically tested instructional model for improving cognitive learning outcomes among preservice elementary school teachers.